ANALYSIS OF POVERTY STATUS AND ALLEVIATIONS STRATEGIES AMONG RURAL FARMING HOUSEHOLD IN POTISKUM LOCAL GOVERNMENT AREA OF YOBE STATE, NIGERIA - Abdulhamid, H.; Onu, J. I.; Tashikalma, A. K. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study aimed to analyse poverty status among rural farming households in Potiskum, Yobe State, Nigeria. A multistage sampling was used in selecting 118 respondents. Data were collected through structured questionnaires and analysed using descriptive statistics and Foster, Greer and Thorbecke (FGT) model. The study used two-thirds of the mean per capita household expenditures on food and non-food items to construct poverty lines. The average monthly expenditure on food and non-food items was ₦31,350.85 and ₦17,227.12, respectively. Majority (83.05%) of the respondents experienced food shortage, and averages of 2 children per household were not enrolled in school. In addition 37.29% of respondents had no access to health centre in their community while 74.58%, 34.75%, 77.12%, 88.14% had their source of water supply from wells, no access to electricity, lived in mud houses with toilets, no access to extension services respectively. FGT model revealed a poverty incidence of 0.4068, poverty depth of 0.1158 and poverty severity of 0.0442. Strategies for poverty reduction include wage labour (51.69), selling produce (35.59), and borrowing inputs (41.53) among others. These shows that substantial portion of the respondents lived in poverty in the study area. Governments should provide credit facilities, extension services, electricity, and medical facilities to rural farming households to reduce poverty incidence in the study area. Formation of cooperative societies should be encouraged. And free education for out-of-school children should be provided.